Peran Kode Etik Guru dalam Meningkatkan Mutu Pembelajaran Berdasarkan Yohanes 13:12-15 - Ayu Lestari, Reysti; Deak, Victor (Harati: Jurnal Pendidikan Kristen, 2023)
This study aims to determine the role of the teacher's code of ethics in improving the quality of Christian education learning based on John 13:12-15 in schools. This study uses a qualitative method. The results of the study show that the role of the teacher's code of ethics in schools. Christian Religious Education has been well implemented, but there are still some obstacles in the role of a code of ethics in improving the quality of Christian religious education. These obstacles include the lack of socialization of the teacher's code of ethics to teachers, the teacher's lack of understanding of the teacher's code of ethics, and the lack of sanctions given to teachers who violate the code of ethics. To improve the quality of education, PAK educational institutions must apply John 13:12-15 as a guideline, namely to increase teacher competency through training and seminars, apply innovative learning methods, and develop a quality evaluation system. From the results of this study it is suggested for schools to further increase socialization regarding the role of the teacher's code of ethics, increase teachers' understanding of the code of ethics, and provide strict sanctions to teachers who violate the code of ethics.